2012
DOI: 10.3171/2012.2.peds11285
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord ependymomas and myxopapillary ependymomas in the first 2 decades of life: a clinicopathological and immunohistochemical characterization of 19 cases

Abstract: Object Primary spinal cord ependymomas (EPNs) are rare in children, comprising classical WHO Grade II and III tumors and Grade I myxopapillary ependymomas (MEPNs). Despite their benign histology, recurrences and neural-axis dissemination have been reported in up to 33% MEPNs in the pediatric population. Treatment options beyond resection are limited, and little is known about their tumorigenesis. The purpose of this study was to explore the tumor biology and outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 21 publications
(30 reference statements)
2
30
0
1
Order By: Relevance
“…8 In a 2012 retrospective single-institution study (n = 11 Grade II ependymomas), Stephen et al reported 100% PFS and OS after a mean of 51 months of follow-up. 62 In a 2013 literature review of more than 30 series (n = 43 Grade II ependymomas), Safaee et al reported a 5-year OS of greater than 90% and a PFS of approximately 80%. 59 This study found that females were much more likely to survive than males among pediatric subjects with Grade II spinal ependymoma.…”
Section: Characteristics and Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 In a 2012 retrospective single-institution study (n = 11 Grade II ependymomas), Stephen et al reported 100% PFS and OS after a mean of 51 months of follow-up. 62 In a 2013 literature review of more than 30 series (n = 43 Grade II ependymomas), Safaee et al reported a 5-year OS of greater than 90% and a PFS of approximately 80%. 59 This study found that females were much more likely to survive than males among pediatric subjects with Grade II spinal ependymoma.…”
Section: Characteristics and Demographicsmentioning
confidence: 99%
“…7,42 They are slow-growing, indolent tumors with a benign course; in the literature, rates of both overall survival (OS) and progression-free survival (PFS) at 5 years have been reported at 90%-100%. 7,42,62 Maximal resection is generally agreed to be the cornerstone of treatment for pediatric spinal ependymomas; 2,7,8,34,42,47,50 however, the addition of adjuvant radiation therapy after surgery is the subject of more debate. 2,7,8,48 While there are many studies on spinal ependymomas in adults, 11,12,[16][17][18]21,24,25,38,41,45,51,56,57,61,65 there are few papers on these tumors in children, and those that do exist tend to be small, single-institution retrospective studies that are not powered for statistical analysis stratified by tumor grade.…”
mentioning
confidence: 99%
“…12,20,25,30,31,34 Six articles specifically described the location of the tumor with respect to the filum terminale and were included in a separate subgroup analysis. 9,10,13,17,35,36 …”
Section: Data Extractionmentioning
confidence: 99%
“…1,6,16,23,[27][28][29]32 In total, 28 articles with 475 patients were included in this integrative analysis. [2][3][4][5][7][8][9][10][11][12][13][14][15][17][18][19][20][21][23][24][25][26]30,31,[34][35][36][37] …”
Section: Article Selectionmentioning
confidence: 99%
“…A recent literature review on pediatric spinal cord myxopapillary ependymomas reported GTR in 60% of cases, but similar recurrence rates when comparing GTR (40%) to STR (43%) at an average follow-up of 77 months. 48 Furthermore, a recent review of our institutional data suggests that extent of resection is associated with improved tumor control among Grade II ependymomas, but not Grade I ependymomas. 49 The study also reported 7 deaths (8%), while we had no deaths due to surgery or disease among both Grade I and Grade II ependymomas.…”
Section: Discussionmentioning
confidence: 99%